2005
DOI: 10.5713/ajas.2005.1407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Undegradable Dietary Protein Level and Plane of Nutrition on Lactation Performance in Crossbred Cattle

Abstract: An experiment was conducted in order to assess the effect of level of RDP:UDP ratio and level of feeding concentrate on milk yield, milk composition and nutrient utilization in lactating crossbred cattle. Twenty four medium producing (~10 kg/d, 45 to 135 days postpartum) lactating crossbred cows were divided into four groups of six animals each in a 2×2 factorial completely randomized design. The cows in group 1 were fed concentrate mixture I containing 59:41 RDP:UDP ratio (low UDP) at normal plane (LUDP+NP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
(20 reference statements)
4
7
3
Order By: Relevance
“…The results of the present study supported the findings of Kumar et al (2005) who reported 13.7% increase in milk production in crossbred cattle when dietary RUP increased from 41 to 48 of dietary CP. Chaturvedi and Walli, (2001) also reported increased (8.2%) milk yield with increasing dietary RUP from 29 to 56%.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study supported the findings of Kumar et al (2005) who reported 13.7% increase in milk production in crossbred cattle when dietary RUP increased from 41 to 48 of dietary CP. Chaturvedi and Walli, (2001) also reported increased (8.2%) milk yield with increasing dietary RUP from 29 to 56%.…”
Section: Resultssupporting
confidence: 82%
“…Increase rate of fiber digestion by dairy cows fed diets containing increased RUP was also noticed (Lallo, 1996). In another study (Kumar et al, 2005) CP, DM and NDF digestibility increased with increasing dietary RUP of CP from 41 to 48%. Similar findings were also reported by Pattanaik et al (2003) in calves where NDF digestibility enhanced by increasing RUP level from 45 to 51% of dietary CP.…”
Section: Resultsmentioning
confidence: 81%
“…These results agreed with Kumar et al (2005), who found that fat yield did not differ significantly among planes of nutrition. These results are in contrast with Weerasinghe et al (2012), who found that the milk fat yield was increased by 15% (P<0.001) in ewes receiving the high metabolizable protein diet.…”
Section: Fat Yieldsupporting
confidence: 92%
“…The higher milk yield in bypass protein supplemented cows may be due to increased supply of amino acids for absorption in small intestine. Similar results of increased milk yield fed with by-pass protein were presented by (Kunju et al,1990;Kumar et al, 2006).Similarly, Chaturvedi et al (2001), Schor (2001), Garg et al (2002a), Garg et al (2003b) and Mishra et al (2006) recorded significantly higher average milk yield in cows due to supplementation of bypass protein. Milk composition: Average milk fat percentage for groups T 0 , T 1 and T 2 was 5.52, 5.55 and 4.47%, respectively.…”
Section: Resultssupporting
confidence: 65%